Flowering in Persian walnut: patterns of gene expression during flower development - Amin Hassankhah; Majid Rahemi; Hossein Ramshini; Saadat Sarikhani; Kourosh Vahdati (BMC Plant Biology, 2020)
Abstract Background Flower development and sufficient fruit set are important parameters with respect to walnut yield. Knowledge about flowering genes of fruit trees can help to conduct better molecular breeding programs. Therefore, this study was carried out to investigate the expression pattern of some flowering genes (FT, SOC1, CAL, LFY and TFL1) in Persian walnut (cv. Chandler) during the growing season and winter dormancy. Results The results showed that walnut flower induction and initiation in Shahmirzad, Iran occurred in early June and late September, respectively. After meeting chilling and heat requirement, flower differentiation and anthesis occurred in late-March and mid-April to early-May, respectively. Study of flowering gene expression showed that the expression of the FT gene increased in three stages including before breaking of bud dormancy, from late March to late April (coincided with flower differentiation and anthesis) and from late May to mid-June (coincided with flower induction). Like FT, the expression of SOC1 gene increased during flower induction and initiation (mid-May to early-August) as well as flower anthesis (mid-April to early-May). LFY and CAL genes as floral meristem identity genes are activated by FT and SOC1 genes. In contrast with flowering stimulus genes, TFL1 showed overexpression during winter dormancy which prevented flowering. Conclusion The expression of FT gene activated downstream floral meristem identity genes including SOC1, CAL and LFY which consequently led to release bud dormancy as well as flower anthesis and induction. Also, TFL1 as a flowering inhibitor gene in walnut showed overexpression during the bud dormancy. Chilling accumulation reduced TFL1 gene expression and increased the expression of flowering genes which ultimately led to overcome dormancy.